Factibilidad de una planta procesadora y comercializadora de pasta de aguacate (persea americana), en el cantón Chone - Mera Varela, Nelson Fabricio (2013)
The present feasibility study for creating a processing plant and marketing the avocado paste (Perseaamericana) inChone canton; it was determined the feasibility of the project, through a market research, technical, financial and environmental analysis, the product selected for installation of the plant was the avocado paste, the product will have a presentation in high density resistant plastic package. Research results show 82% acceptance (18340 lb / month as total demand). We determined the consumer profile, comparing an existing product in the market, and this is an innovative product. The technical study determined that the optimal size of the processing plant is 321.50 m2 and the production quantity was determined that the plant will feature: 5 workers, a secretary, a technical production chief and it will be located in the Chone Canton. The financial study revealed an NPV of $ 22.409,24 and an IRR of 22.04%, this indicates that the project is viable, even according to the projections, the proposed agribusiness can be financed by the National Financial Corporation with 67% of capital and 33% by the authors. The Leopold matrix presented 25 positive environmental impacts and 14 negative impacts. Finally we conclude that this company is feasible to implement it considering the positive results during the development of the proposal.